ANALYSIS OF THE EFFECT OF DIVIDEND PAYMENTS, GLOBAL FINANCIAL CRISIS, INTERNAL FINANCE, AND EXTERNAL FINANCE ON COMPANY SALES GROWTH IN INDONESIA - Elita Permanawati; Masyhuri Hamidi; Fajri Adrianto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This study aims to determine the effect of dividend payments, the global financial crisis, internal finance, and external finance on the company's sales growth in Indonesia. There are several control variables such as size, leverage, profitability, and past growth assets. The reason for taking this research sample in Indonesia is because Indonesia is one of the developing countries whose economy is currently growing even though it is being hit by the Covid 19 pandemic. Investment is a good climate in Indonesia for sales growth. And also still few studies describe this research. The sample used is the consumer goods sector companies listed on the IDX for the 2016-2020 period as many as 21 companies selected using purposive sampling technique. This study uses panel data regression analysis and moderated regression analysis (MRA). The results showed that dividend payments influenced the company's sales growth. Meanwhile, the variables of the global financial crisis, internal finance and external finance had no effect on the company's sales growth. Then the variables of size, leverage, profitability, and past assets as control variables have no effect on the company's sales growth as control variables.